Dialogic pedagogical innovation: Creating liberating learning practices for first year university students - Mudehwe-Gonhovi, F.R.; Galloway, G.; Moyo, G. (South African Journal of Higher Education, 2019)
Liberatory and emancipatory thinking is shaped by a de-colonised approach to university teaching practices supported by literature on dialogic pedagogy. A theoretical framework for this paper is shaped by the critical realism views of Archer’s (2010) presented through the morphogenetic phases. At this particular university the grounding programme is a compulsory first year inter-disciplinary module called Life, Knowledge and Action (LKA) aimed at promoting liberating practices through dialogic pedagogy. Interpretive and critical approaches were adopted, using mixed methods questionnaires, interviews and observations for data collection. The findings show that LKA was extremely liberating when students became contributors to knowledge creation. Students claimed/expressed their views stating that dialogue liberated them as it exposed them to diverse and alternative views and opinions. Considering the LKA aims the study recommends that the course be offered throughout undergraduate duration as it might be difficult to achieve all goals within a year.